Characteristic and Otopathogenic Analysis of a Vibrio alginolyticus Strain Responsible for Chronic Otitis Externa in China - Zhou, Ke; Tian, Ke-yong; Liu, Xin-qin; Liu, Wei; Zhang, Xin-yu; Liu, Jia-yun; Sun, Fei (Frontiers in Microbiology, 2021)
Vibrio alginolyticus, a Gram-negative rod bacterium found in marine environments, is known to cause opportunistic infections in humans, including ear infections, which can be difficult to diagnose. We investigated the microbiological and otopathogenic characteristics of a V. alginolyticus strain isolated from an ear exudate specimen obtained from a patient with chronic otitis externa to provide a basis for the future diagnosis of V. alginolyticus–associated infections. The identification of V. alginolyticus was accomplished using a combination of matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS), classical biochemical identification methods, and the use of Vibrio-selective media and advanced molecular identification methodologies. Antimicrobial susceptibility testing revealed that the strain was resistant to ampicillin and sensitive to β-lactam, aminoglycosides, fluoroquinolones, and sulfonamide antibiotics. The potential otopathogenic effects of V. alginolyticus were determined through the performance of cell viability, cell apoptosis, and cell death assays in tympanic membrane (TM) keratinocytes and HEI-OC1 cells treated with V. alginolyticus-conditioned medium using cell-counting kit (CCK)-8 assay, a wound-healing migration assay, Annexin V/propidium iodide flow cytometric analysis, and terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL staining). The results indicated that the identified V. alginolyticus strain exerts cytotoxic effects on keratinocytes and HEI-OC1 cells by inhibiting cell proliferation and migration and inducing apoptosis and cell death. To evaluate the ototoxicity of V. alginolyticus, the cell density and morphological integrity of hair cells (HCs) and spiral ganglion neurons (SGNs) were analyzed after exposing cochlear organotypic explants to the bacterial supernatant, which revealed the predominant susceptibility and vulnerability of HCs and SGNs in the basal cochlear region to the ototoxic insults exerted by V. alginolyticus. Our investigation highlights the challenges associated with the identification and characteristic analysis of the Vibrio strain isolated in this case and ultimately aims to increase the understanding and awareness of clinicians and microbiologists for the improved diagnosis of V. alginolyticus–associated ear infections and the recognition of its potential otopathogenic and ototoxic effects.